Improving coverage method of autonomous drones for environmental monitoring - Yildirim, Omur; Acar Vural, Revna; Diepold, Klaus (Tubitak Scientific & Technological Research Council Turkey, 2020)
With the rapid developments of unmanned aerial vehicles (UAVs), usage of UAVs is increasing to bring autonomy for complicated processes such as environmental monitoring. Because of the complexity of the problem, environmental monitoring tasks are highly demanding in terms of time and resources. To reduce expensive costs of operations, improvements on autonomous observation capabilities has a key role. In this work, we offer coverage improvements for our autonomous environmental monitoring system. We compared different path planning approaches to find out the optimum path planning solution. Simulation results showed that required task execution time and required resources are decreased by usage of improved decomposition of the coverage field.
Keywords: Environmental monitoring; UAV; target detection; complete coverage; path planning; SEARCH; Computer Science; Engineering